2015
DOI: 10.1590/0004-282x20150140
|View full text |Cite
|
Sign up to set email alerts
|

Alpha power oscillation in the frontal cortex under Bromazepam and Modafinil effects

Abstract: Objective Our aim was to investigate and compare the neuromodulatory effects of bromazepam (6 mg) and modafinil (200 mg) during a sensorimotor task analyzing the changes produced in the absolute alpha power.Method The sample was composed of 15 healthy individuals exposed to three experimental conditions: placebo, modafinil and bromazepam. EEG data were recorded before, during and after the execution of the task. A three-way ANOVA was applied, in order to compare the absolute alpha power among the factors: Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…The result suggested that when participants are unmotivated, the complexity of the data between two recognition cases is similar. The areas where we can observe the difference the most are the frontal and around the left PPA areas, which are also consistent with the findings in previous research [ 18 , 23 , 24 , 25 , 26 , 27 ]. These findings allowed us to grasp the global characteristic differences of alpha desynchronization patterns under intrinsic motivation and the locations to place electrodes for detection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The result suggested that when participants are unmotivated, the complexity of the data between two recognition cases is similar. The areas where we can observe the difference the most are the frontal and around the left PPA areas, which are also consistent with the findings in previous research [ 18 , 23 , 24 , 25 , 26 , 27 ]. These findings allowed us to grasp the global characteristic differences of alpha desynchronization patterns under intrinsic motivation and the locations to place electrodes for detection.…”
Section: Discussionsupporting
confidence: 93%
“…The affected channels also coincided with the conventional channels related to the attention task. The frontal area is one of the conventional areas used in EEG cognitive research, which was found to be related to the attention and cognitive performance of subjects [ 23 , 24 ]. The cognitive task with scenery stimulus was also found to cause the activation of the parahippocampal place area (PPA) in the temporal area in fMRI research [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, bromazepam affects perception due to the changes in inputs and neural outputs related to the learning process and muscle relaxation during the execution of visuomotor tasks (Montenegro et al, 2005;Cunha et al, 2006;Machado et al, 2009;Gongora et al, 2014;Aprigio et al, 2015). These effects could be due to increasing the reaction time during the execution of tasks; could induce greater attention level or reduce the mental effort in the performance of motor tasks (Cunha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%